CGIAR Annual Report 2024 - CGIAR System Organization (CGIAR System Organization, 2025)
Our 2024 Annual Report highlights the significant strides made by CGIAR in our ongoing mission to transform food, land, and water systems in a climate crisis. This year’s report focuses on our work to support poverty reduction, livelihoods and jobs.